The Client Capital in Nursing Management in Hospitals - Ana Lúcia Arcanjo Oliveira Cordeiro; Josicélia Dumêt Fernandes; Maria Deolinda Antunes Luz Lopes Dias Mauricio; Rosana Maria de Oliveira Silva; Cláudia Silva Marinho Antunes Barros; Cátia Maria Costa Romano
Abstract Objective: To analyze how the components of the client's capital are used in the management of nursing in hospitals. Method: A qualitative research carried out in five public hospitals, four private hospitals and three philanthropic hospitals in the period from October 2014 to May 2015. Data were collected through a semi-structured interview with twelve nursing managers and analyzed according to content analysis. Results: The components of the Client's Capital were used by the nurses when performing the management of the client service to promote changes and improve the service after evaluating the satisfaction of the nursing care through active systematic search, with its own evaluation tools and the ombudsman's information and in the interaction with suppliers of materials, equipment and services. Conclusion and implications for practice: The managers use managerial actions for the development of the client's capital of organizations. In order to improve them, they must evaluate the nursing care in a continuous and strategic process to satisfy the clients, throughout their trajectory in the organization, since clients are permanent sources of innovation that affect professional and organizational development and productivity.